Pacta Sunt Servanda Principles: Implementation in Agreements Managing Unanticipated Circumstances - Dahris Siregar; Karolina Sitepu; Khairun Na’im (CV Tirta Pustaka Press, 2026)
Conventional law is built on the idea of pacta sunt servanda, which means that both sides must follow through on their deal. The study analyzes the application and limits of the pacta sunt servanda principle in cases of unforeseen circumstances, particularly economic hardship, and the legal protection available to the parties. This study uses a normative legal approach by examining contract law provisions, the doctrine of hardship, and selected Indonesian Supreme Court decisions over the past decade. Although the pacta sunt servanda concept is formally binding, it can be overturned in very rare cases of foresight, the ideals of good faith and suitability, as well as Article 1338 paragraph 3 of the Civil Code.Although Article 1338(1) of the Civil Code affirms that agreements are binding, the pacta sunt servanda principle is not absolute and must be balanced with fairness and good faith. Indonesian judges have a tendency to recognize although the theory of unforeseen circumstances is meant to stop extreme unfairness, the most important rule for keeping commercial ties steady and clear is still